Guidelines for diagnosis and treatment in neurology – Lyme neuroborreliosis - Rauer, Sebastian; Kastenbauer, Stephan; Hofmann, Heidelore; Fingerle, Volker; Huppertz, Hans-Iko; Hunfeld, Klaus-Peter; Krause, Andreas; Ruf, Bernhard; Dersch, Rick; Consensus group (GMS German Medical Science, 2020)
Lyme borreliosis is the most common tick-borne infectious disease in Europe. A neurological manifestation occurs in 3–15% of infections and can manifest as polyradiculitis, meningitis and (rarely) encephalomyelitis.This S3 guideline is directed at physicians in private practices and clinics who treat Lyme neuroborreliosis in children and adults.Twenty AWMF member societies, the Robert Koch Institute, the German Borreliosis Society and three patient organisations participated in its development. A systematic review and assessment of the literature was conducted by the German Cochrane Centre, Freiburg (Cochrane Germany).The main objectives of this guideline are to define the disease and to give recommendations for the confirmation of a clinically suspected diagnosis by laboratory testing, antibiotic therapy, differential diagnostic testing and prevention.